2015
DOI: 10.1007/s11605-015-2814-3
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of CEA Levels Post-Neoadjuvant Therapy is a Strong Predictor of Pathologic Complete Response in Rectal Cancer

Abstract: Low post-nCRT CEA is an independent predictor of pCR, and normalization of CEA post-nCRT is a strong predictor of pCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 24 publications
2
45
1
7
Order By: Relevance
“…As for the relation between the serum CEA level after nCRT and the histologic response, some studies have reported a high rate of ypCR among patients with negative serum CEA levels [22,23,37], whereas another study found no relation between the serum CEA level after nCRT and response [24]. Consistent results have thus not been obtained.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As for the relation between the serum CEA level after nCRT and the histologic response, some studies have reported a high rate of ypCR among patients with negative serum CEA levels [22,23,37], whereas another study found no relation between the serum CEA level after nCRT and response [24]. Consistent results have thus not been obtained.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have reported that the serum CEA level before nCRT is related to the histologic response [9,20,21], whereas another study found no relation between these factors [22]. The serum CEA level after nCRT has been reported to be related to the treatment response by some studies [22,23], whereas another study found no relation between these factors [24]. In patients with rectal cancer who receive CRT, the clinical significance of serum CEA as a predictor of the treatment response and outcomes has not been established.…”
mentioning
confidence: 99%
“…Numerous retrospective cohort studies have previously examined this question and have identified a variety of disease-related variables as potential predictors of pCR. These include low pre-therapy CEA, 17,21,26, 28,37,38 low CEA after nCRT, 29, 35 small pre- 31,38 and post-treatment tumor size, 22 pre-treatment tumor ‘movability’, 22 low N category, 31 low tumor grade, 36 shorter distance from the anal verge, 18,36 smaller circumferential tumor extent, 18,28 and low neutrophil to lymphocyte ratio. 38 Identification and awareness of these factors may help to predict which patients are more likely to achieve pCR with neoadjuvant treatment, and may be used to counsel patients more accurately regarding their prognosis and treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…However, not only the pre-CRT CEA level but also the post-CRT CEA level, and/or the change in the CEA pattern after CRT, are often analyzed together. The latter two measures are more closely related to the pathological CRT response than is the pre-CRT CEA level [58][59][60]. This is not surprising because the latter values reflect the degree of CRT response.…”
Section: Predictive Markers Clinicopathological Factorsmentioning
confidence: 91%